Good management practices in rice field among progressive farmers in northwestern region of Selangor - Hassan, Salim; Asmuni, Azizan; Md. Sail, Rahim; Ahmad, Aminah; Abu Samah, Bahaman; Ismail, Ismi Arif (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
The objective of this research is to understand who and how paddy progressive farmers in northwestern region of Selangor manage their paddy crop until they achieved high productivity yield. Data were collected by using the method of face-to-face detailed interviews. The research has produced six main themes which represent Progressive farmers, that are;(1) Progressive farmers have low academic qualification;(2) Progressive farmers made their paddy area as their main source of income;(3) Progressive farmers manages their own paddy area;(4)Progressive farmers have 9 positive personalities. The personalities of the Progressive farmers are similar to the Innovators group (Rogers, 2003), with a few new personalities.(5) Progressive farmers practices good agricultural practice and fulfil four high performance yield indicators; and finally (6) Progressive farmers achieved high yield productivity and gained high income.